2021
DOI: 10.3390/diagnostics11122203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Epiretinal Membrane on Optical Coherence Tomography Tools Used for Monitoring Glaucoma

Abstract: Background: Retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) measurements can be influenced by many factors including the presence of concomitant retinal diseases. The aim of this study it to assess the impact of epiretinal membrane (ERM) on RNFL and GCL assessment using optical coherence tomography (OCT). Methods: GCL, peripapillary RNFL (pRNFL), and Bruch’s Membrane Opening Minimum Rim Width (BMO-MRW) thicknesses were analysed using an SD-OCT (Spectralis OCT) in eyes with idiopathic ERM and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several studies reported the impact of ERM on the thickness measurement of the macular area and peripapillary RNFL using OCT [ 22 , 23 , 24 , 25 ]. An ERM usually involves the macula, centers on the perifovea, and often extends to the peripapillary area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported the impact of ERM on the thickness measurement of the macular area and peripapillary RNFL using OCT [ 22 , 23 , 24 , 25 ]. An ERM usually involves the macula, centers on the perifovea, and often extends to the peripapillary area.…”
Section: Discussionmentioning
confidence: 99%
“…Nam et al revealed that the repeatability of the measurement of peripapillary RNFL thickness performed by SD-OCT was fair, even in patients who had an ERM with peripapillary involvement [ 25 ]. Some studies showed that the temporal and global peripapillary RNFL thicknesses were significantly higher than those of normal controls [ 23 , 24 ]. In particular, the thickening in temporal and global peripapillary RNFL was much higher in patients who had an ERM that extended to the peripapillary area [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation